Mutual investment funds as actively developing direction of investment attraction - A. S. Bershakova (Путеводитель предпринимателя)
In today’s investment system, the special role is played by mutual investment funds, which over the past few year have become especially popular with a mass investor and have become one of the competitors of bank deposits. The author considers the features of the functioning of mutual investment funds and outlines the main steps that will help the investor in choosing a mutual fund.